2007
DOI: 10.1007/s00464-007-9616-y
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic-assisted proctocolectomy using complete intracorporeal dissection

Abstract: A complete laparoscopic proctocolectomy dissection is feasible and safe for surgical treatment of UC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…In our study, no patients developed a wound infection, as the incision was minimal. The median operation time in our study was longer than that reported for HALS in recent studies of UC, but was similar to that for straight LTP in other series (5,13–19) (Table 4). The mean blood loss volume was less than in other series, and no patient required a blood transfusion in any of these studies.…”
Section: Discussionsupporting
confidence: 88%
“…In our study, no patients developed a wound infection, as the incision was minimal. The median operation time in our study was longer than that reported for HALS in recent studies of UC, but was similar to that for straight LTP in other series (5,13–19) (Table 4). The mean blood loss volume was less than in other series, and no patient required a blood transfusion in any of these studies.…”
Section: Discussionsupporting
confidence: 88%
“…Other authors also report using this approach to proctectomy for IBD. 14 Rink et al, on the other hand, prefer to preserve the mesorectal fat when performing IPAA for patients with ulcerative colitis, citing a lower rate of local septic complications. 15 This, however, has not been verified in a comparison study, and most reports in the literature do not specify the technique for rectal dissection for benign disease, making a retrospective analysis difficult.…”
Section: Discussionmentioning
confidence: 99%
“…When TME was compared with conventional rectal cancer surgery, the local and overall recurrence rate after surgery decreased from 25% to 5% and from 62% to 22%, respectively [1,2]. The mesorectal plane is anatomically based and bloodless, so this dissection plane is also used in the treatment of a wide variety of colorectal pathologies, including inflammatory bowel disease or rectal prolapse, especially in cases where a laparoscopic approach is used [3,4].…”
Section: Introductionmentioning
confidence: 99%